The Use of Islamic Attribute in Food Products Marketing: Expert Views - Suraiya Osman; Suhaimi Ab. Rahman; Elistina Abu Bakar; Yasmin Hanani Mohd Safian (Malaysian Association of Consumer and Family Economics (MACFEA), 2024)
Non- Index Publication